Bioactive Compounds as Potential Agents for Sexually Transmitted Diseases Management: A Review to Explore Molecular Mechanisms of Action - Sharifi-Rad, Javad; Quispe, Cristina; Rahavian, Amirhossein; Pereira Carneiro, Joara Nályda; Rocha, Janaína Esmeraldo; Alves Borges Leal, Antônio Linkoln; Bezerra Morais Braga, Maria Flaviana; Melo Coutinho, Henrique Douglas; Ansari Djafari, Anahita; Alarcón-Zapata, Pedro; Martorell, Miquel; Antika, Gizem; et al. (Frontiers in Pharmacology, 2021)
Sexually transmitted diseases (STDs) are produced by pathogens like bacteria, fungi, parasites, and viruses, and may generate severe health problems such as cancer, ulcers, and even problems in the newborn. This narrative review aims to present updated information about the use of natural bioactive compounds for the prevention and treatment of sexually transmitted infections. A search of the literature was performed using databases and search engines such as PubMed, Scopus, Google Scholar and Science Direct. From the pharmacotherapeutic management point of view, any strategies for effective prevention should contain medical approaches. The bioactive compounds obtained from natural products have shown biological effectiveness against different microorganisms for the treatment of these diseases. The main results showed antimicrobial, antiprotozoal, antifungal and antiviral effects such as HIV. Also, the molecular mechanisms, signalling pathways and action targets of natural compounds were highlighted, thus justifying bacterial and antifungal inhibition, apoptosis or reduction of viral replication. From the data of our study, we can conclude that natural compounds may be a significant source for adjuvant drugs / complementary therapies in the treatment of STDs. With all these benefits, the future must conduct extensive clinical trials and the development of pharmaceutical nanotechnologies for a greater therapeutic effect.